Analisis Nilai Tambah, Profitabilitas dan Sensitivitas Agroindustri Penyulingan Minyak Daun Cengkeh di Kabupaten Bone: Studi Kasus Usaha Kamsir dan Usaha Agustan di Desa Abbumpungeng, Kecamatan Cina - A.Nurhaliza (LPPM Universitas Malikussaleh - Indonesia, 2025)
Cloveleaf oil distillation is an agroindustrial business that utilizes agricultural waste in the form of dried clove leaves into a high-value product. Cloveleaf oil has broad market potential, particularly in the pharmaceutical, cosmetic, and aromatherapy sectors. The objectives of this study are: (1) to describe the cloveleaf oil distillation process; (2) to analyze the yield of clove leaves into oil; (3) to analyze the added value generated; (4) to calculate the income from cloveleaf oil distillation; (5) to analyze the profitability level; and (6) to analyze the sensitivity of selling prices to profitability. The methods used include descriptive analysis to describe the production process, yield analysis, added value analysis, income analysis, and profitability analysis through the Break-Even Point (BEP) approach (in units and rupiah), comparison of the Margin of Safety (MOS) and Margin Income Ratio (MIR), as well as sensitivity analysis. The results show that the cloveleaf oil distillation process in Enterprises 1 and 2 in Abbumpungeng Village consists of five main stages: raw material preparation, distillation, cooling, filtering, and packaging. The resulting yield is 1.95% (moderate category). The added value reaches 65.7% (high category). The average monthly income is Rp38,727,750, with a profitability level of 38.2% (moderate category). Sensitivity analysis results in a value of 1 (quite sensitive), indicating that changes in selling prices significantly affect the profitability of cloveleaf oil distillation businesses in Abbumpungeng Village, Cina District, Bone Regency.